Síndrome coronario agudo sin supradesnivel ST. Diagnóstico y tratamiento inicial - Ugalde P., Héctor (Revista Hospital Clínico Universidad de Chile, 2018)
Coronary heart disease can manifest as stable or unstable forms, being these variations differentiated mainly by the underlying pathophysiological cause, their clinical presentation and the risk associated to each of these clinical presentations. In the unstable form, nowadays known as acute coronary syndrome, recommendations over its characterization and particularly its management are periodically updated in published international guidelines about this topic. Their epidemiological relevance makes important that these aspects should be known by anyone that sees patients in their practices, motivating this review in which we will summarize aspects of the clinical presentation, initial studies and management of the acute coronary syndrome without ST segment elevation emphasizing novelties from the last few years.